2020
DOI: 10.1590/1981-22562020023.200198
|View full text |Cite
|
Sign up to set email alerts
|

Velhice, trabalho e saúde do trabalhador no Brasil: uma revisão integrativa

Abstract: Resumo Objetivo Discutir a relação entre a velhice, o trabalho e a saúde do trabalhador no Brasil, a partir de produções científicas brasileiras obtidas de uma revisão integrativa. Método e resultados: Definidos uma pergunta norteadora e critérios para a busca, realizou-se uma pesquisa nas bases de dados Scientific Electronic Library Online (SCIELO), Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), Biblioteca Digital Brasileira de Teses e Dissertações (BDTD). No total de 341 produções e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
(11 reference statements)
0
4
0
2
Order By: Relevance
“…Older persons in better economic positions have greater QoL than those in worse economic situations (Algahtani et al, 2021). In Brazil, people are encouraged to continue working to an older age, and there are approximately 7.5 million older persons in the workforce (Pazos & Bonfatti, 2020). Work activity helps the formation of self-identity among senior Brazilians, which includes self-esteem and a sense of usefulness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older persons in better economic positions have greater QoL than those in worse economic situations (Algahtani et al, 2021). In Brazil, people are encouraged to continue working to an older age, and there are approximately 7.5 million older persons in the workforce (Pazos & Bonfatti, 2020). Work activity helps the formation of self-identity among senior Brazilians, which includes self-esteem and a sense of usefulness.…”
Section: Discussionmentioning
confidence: 99%
“…Work activity helps the formation of self‐identity among senior Brazilians, which includes self‐esteem and a sense of usefulness. Furthermore, in the contemporary Brazilian context, the older people 's persistence in work is heightened by the new public pension system, which significantly increased the minimum retirement age of employees (Pazos & Bonfatti, 2020). In our study, participants who did not change their work conditions due to COVID‐19 showed higher QoL (Duan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…-A relação entre a velhice, o trabalho e a saúde do trabalhador foi discutida; além da incipiência de estudos sobre o tema, encontrou-se uma baixa efetividade das políticas públicas no âmbito do direito ao trabalho para as pessoas idosas brasileiras (27) ; -As publicações referentes ao cenário do mundo do trabalho para pessoas idosas e às situações de violência enfrentadas foram avaliadas; as pessoas idosas apresentam dificuldades para trabalhar devido às inadequações do ambiente laboral e pela sua própria condição de saúde. No que respeita à violência sofrida no trabalho apesar da escassez de estudos destacam-se as dificuldades de entrada e permanência no mercado de trabalho (28) ; -Os principais documentos internacionais que tratam do direito da pessoa idosa ao trabalho, assim como as estratégias para garanti-lo evidenciaram os fundamentos para a elaboração e a implementação de políticas públicas e programas institucionais/ empresariais dirigidos à pessoa idosa (29) ;…”
Section: A Pessoa Idosa E O Mundo Do Trabalhounclassified
“…The ILO, in the document "World Employment and Social Perspectives" (ILO, 2018), considers that factors, such as working conditions, the productivity of elderly people, the pension system, and social assistance, must be reformulated in view of the need for the sustainability of this group within the economically active population. Taking into account that much elderly use to return to the labor market in order to complement their income and that old age tends to be related to situations of vulnerability, it is necessary to ensure to elderlies the right to access the labor market as a way to contribute to their human dignity, associated to the labor life planning in all cycles of work (Pazos & Bonfatti, 2020;Dell'isola et al, 2020).…”
Section: Introductionmentioning
confidence: 99%